Statistical Physics of Non-Thermal Phase Transitions : From Foundations to Applications - Abaimov, Sergey G. (Springer Series in Synergetics,, 2015)
Statistical physics can be used to better understand non-thermal complex systems-phenomena such as stock-market crashes, revolutions in society and in science, fractures in engineered materials and in the Earth's crust, catastrophes, traffic jams, petroleum clusters, polymerization, self-organized criticality and many others exhibit behaviors resembling those of thermodynamic systems. In particular, many of these systems possess phase transitions identical to critical or spinodal phenomena in statistical physics. The application of the well-developed formalism of statistical physics to non-thermal complex systems may help to predict and prevent such catastrophes as earthquakes, snow-avalanches and landslides, failure of engineering structures, or economical crises. This book addresses the issue step-by-step, from phenomenological analogies between complex systems and statistical physics to more complex aspects, such as correlations, fluctuation-dissipation theorem, susceptibility, the concept of free energy, renormalization group approach and scaling. Fractals and multifractals, the Ising model, percolation, damage phenomena, critical and spinodal phase transitions, crossover effects and finite-size effects are some of the topics covered in Statistical Physics of Non-Thermal Phase Transitions.